Vocabulary Formation in Altafheem and Danishnama - Rahela Hamidzai (̒Ilm-i Zabān, 2016)
Dari Persian language, due to the increased amalgamation with Arabic language and acceptance of a number of new scientific, literary, religious, political terminologies and applying them in various poetical works and concepts, developed considerably in the 4th and early 5th centuries (Hijri calendar) compared to 3rd century (Hijri calendar). As for the language used by poets and writers of this period compared with the subsequent literary period, fewer Arabic words and more original Dari Persian and Pahlavi language words can be observed. It should be stated that the poets and writers of this period were less influenced by Arabic grammatical rules and they were mostly observing Persian grammatical rules. Many scholars sought to write their works in Persian or use Persian equivalents to Arabic words. Avicina Balkhi and Abu-Rayhan Alberoni were two prominent scholars who strongly promoted the use of Dari Persian language.